Utility and Cost Effectiveness of Routine, Histologic Evaluation of the Mastectomy Scar in Two-Stage, Implant-Based Reconstruction during Expander-to-Implant Exchange. Issue 6 (December 2018) - Fishman, Jordan E.; Pang, John Henry Y.; Dabbs, David; De La Cruz, Carolyn
Abstract : Background: Routine histologic analysis of the mastectomy scar is well studied in the delayed breast construction population; no data regarding its utility in the immediate, staged reconstruction cohort have been published. Methods: A retrospective review of all of the senior author's (C.D.C.) patients who underwent immediate, staged reconstruction was performed. The mastectomy scar was analyzed routinely at the time of expander-to-implant exchange. Six hundred forty-seven breasts were identified. The mastectomy scar, time between expander and permanent implant, average patient age, and mastectomy indication were calculated. A cost analysis was completed. Results: All scar pathologic results were negative for in-scar recurrence. The majority, 353 breasts, underwent mastectomy for carcinoma, 94 for germline mutations, 15 for high-risk lesions, six for high family risk, and 179 for contralateral symmetry/risk reduction. The average age at mastectomy/expander placement was 47.7 ± 10.3 years, and the average time between expander placement and implant exchange was 254 ± 152 days. The total histologic charge per breast was $602. Conclusions: A clinically silent in-scar recurrence is, at most, a rare occurrence. Routine histologic analysis of the mastectomy scar can be safely avoided in the immediate, staged reconstruction cohort. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.